The relationship between interpersonal communication skills and job performance among practical trainees at UiTM Sarawak/ Mary Patricia Patrick - Patrick, Mary Patricia (2016)
The objective of this study was to investigate relationship between interpersonal communication skills and job performance among practical training at UiTM Sarawak. The study was to examine the climate of practical training in selected organizations. Correlation analyses were conducted to examine the associations of trainees’ interpersonal communication skills and job performance. 140 out of 156 trainees responded to the questionnaires provided. This study was able to help trainees in improving their interpersonal communications skills in order to achieve better job performance in workplaces.